The impact of transient and persistent acute kidney injury in hospital mortality in COVID-19 patients - Bernardo,João (2021)
Abstract Introduction: Acute kidney injury (AKI) has been described in Coronavirus Disease 2019 (COVID-19) patients and is considered a marker of disease severity and a negative prognostic factor for survival. In this study, the authors aimed to study the impact of transient and persistent acute kidney injury (pAKI) on in-hospital mortality in COVID-19 patients. Methods: This was a retrospective observational study of patients hospitalized with COVID-19 in the Department of Medicine of the Centro Hospitalar Universitario Lisboa Norte, Lisbon, Portugal, between March 2020 and August 2020. A multivariate analysis was performed to predict AKI development and in-hospital mortality. Results: Of 544 patients with COVID-19, 330 developed AKI: 166 persistent AKI (pAKI), 164 with transient AKI. AKI patients were older, had more previous comorbidities, had higher need to be medicated with RAAS inhibitors, had higher baseline serum creatine (SCr) (1.60 mg/dL vs 0.87 mg/dL), higher NL ratio, and more severe acidemia on hospital admission, and more frequently required admission in intensive care unit, mechanical ventilation, and vasopressor use. Patients with persistent AKI had higher SCr level (1.71 mg/dL vs 1.25 mg/dL) on hospital admission. In-hospital mortality was 14.0% and it was higher in AKI patients (18.5% vs 7.0%). CKD and serum ferritin were independent predictors of AKI. AKI did not predict mortality, but pAKI was an independent predictor of mortality, as was age and lactate level. Conclusion: pAKI was independently associated with in-hospital mortality in COVID-19 patients but its impact on long-term follow-up remains to be determined.